MOLECULAR BARCODING REVEAL THE EXISTENCE OF MOLE CRABS EMERITA EMERITUS IN NORTH COAST OF CENTRAL JAVA - Bhagawati, Dian; Winarni, Elly Tuti; Nuryanto, Agus (Biosaintifika: Journal of Biology & Biology Education, 2020)
The existence of mole crabs had been reported from the southern coast of Central Java. However, no mole crab data was available from the northern coast Central Java.  This study aimed to figure out the existence of mole crabs in the northern coast of Central Java as revealed from the cytochrome c oxidase 1 (COI) barcoding. Mole crabs samples collected in Sendang Sikucing Beach Kendal. Taxonomic status of the samples was inferred from sequences similarity test using basic local alignment search tool to conspecific sequence deposited in GenBank. Pairwise genetic distances were calculated based on the Kimura 2-parameter model. A phylogenetic tree had reconstructed in molecular evolution genetic analysis (MEGA) software based on neighbor-joining algorithm. Branching reliability was obtained from 1000 bootstraps replication while branching polarity was obtained from the out-group comparison. The mole crab samples from the northern coast of Central Java had unambiguously identified as Emerita emeritus based on high sequences similarities (98.27%-99.70%), low genetic distances (0.002-0.005), and their monophyly with Emerita emeritus (KR047035) in GenBank. Pairwise analysis among each possibility pair of samples had genetic distances ranged between 0.000 and 0.005, indicated that all sample belong to single species. The data provide the first record of the existence of Emerita emeritus in the northern coast of Central Java. Our data on the existence of E. emeritus in the northern coast of Central Java is among essentials information as a scientific basis in creating policy for the management of sustainable use of the mole crabs in the areas.